Educational Psychology-Based Learning Strategies to Support Elementary School-Age Children's Learning - Leni Febriani; Rahmi Sri Rahayu; Livia Arista; Yuliana Yuliana; Muslih Hidayat; Lusi Agustin; Nefi Afila; Masnonah Masnonah; Resi Sapitri; Liza Murniviyanty; Syska Purna Sari; Arizona Arizona (Scidacplus, 2026)
Elementary school children are at a crucial stage of development in cognitive, emotional, social, and moral aspects. Therefore, learning strategies should not only focus on academic achievement but also take into account students' developmental characteristics. Educational psychology plays a significant role in helping educators understand how children learn and the factors influencing learning success. This study aims to examine educational psychology-based learning strategies to support elementary school students. The method used is a literature review analyzing recent scientific journals and books. The results indicate that strategies such as active learning, play-based learning, contextual learning, and individualized approaches can enhance motivation, engagement, and learning outcomes. Thus, integrating educational psychology into teaching is essential for creating effective and meaningful learning experiences.